Priority areas for the conservation of Atlantic forest large mammals - Galetti, Mauro [UNESP]; Giacomini, Henrique C. [UNESP]; Bueno, Rafael S. [UNESP]; Bernardo, Christine S. S. [UNESP]; Marques, Renato M. [UNESP]; Bovendorp, Ricardo S. [UNESP]; Steffler, Carla E. [UNESP]; Rubim, Paulo [UNESP]; Gobbo, Sabrina K. [UNESP]; Donatti, Camila I. [UNESP]; Begotti, Rodrigo A. [UNESP]; Meirelles, Fernanda [UNESP]; et al. (Elsevier B.V., 2009)
Large mammal faunas in tropical forest landscapes are widely affected by habitat fragmentation and hunting, yet the environmental determinants of their patterns of abundance remain poorly understood at large spatial scales. We analysed population abundance and biomass of 31 species of medium to large-bodied mammal species at 38 Atlantic forest sites (including three islands, 26 forest fragments and six continuous forest sites) as related to forest type, level of hunting pressure and forest fragment size using ANCOVAs. We also derived a novel measure of mammal conservation importance for each site based on a Mammalian Conservation Priority index (MP(i)) which incorporates information on species richness, population abundance, body size distribution, conservation status, and forest patch area. Mammal abundance was affected by hunting pressure, whereas mammalian biomass of which was largely driven by ungulates, was significantly influenced by both forest type and hunting pressure. The MP(i) index, when separated into its two main components (i.e. site forest area and species-based conservation index C(i)), ordered sites along a gradient of management priorities that balances species-focused and habitat-focused conservation actions. Areas with the highest conservation priority were located in semi-deciduous forest fragments, followed by lowland forests. Many of these fragments, which are often embedded within large private landholdings including biofuel and citrus or coffee crops, cattle ranches and pulpwood plantations, could be used not only to comply with environmental legislation, but also enhance the prospects for biodiversity conservation, and reduce edge effects and hunting. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Defaunation; Hotspots; Subsistence hunting; Line-transect; Forest fragmentation